This is our place eaudiobook - Martins, Vitor (Scholastic Audio Books, 2022)
Three teens — in three different decades — navigate life, love, and family in Vitor Martinss heartfelt new novel that spans generations. Perfect for fans of Tales from the City and Simon vs. the Homo Sapiens Agenda . If the walls of Number 8 Sunflower Street could talk ... As Ana celebrates the new millennium, she is shocked to learn that she must leave behind her childhood home, her hometown, and — hardest of all — her girlfriend for a new life in Rio de Janeiro. Ten years later, Greg is sent to live with his aunt — who runs a video rental store from her garage and owns a dog named Keanu Reeves — as his parents work out their not-so-secret divorce. And ten years after that, Beto must put his dreams of becoming a photographer on hold as the Covid-19 pandemic arrives in Brazil, forcing him to live with his overprotective mother and overachieving sister. Set in and narrated by the same house, Number 8 Sunflower Street, and in three different decades — 2000, 2010, and 2020 respectively — This Is Our Place is a novel about queer teens dealing with sudden life changes, family conflict, and first loves, proving that while generations change, we will always be connected to each other.